Recycle System in Reading Ability Language English Beginning Child Age Early - Zaharah Binti Awang; A.Zebar; Afdhalina (Outline Publisher, 2024)
Early English reading skills of early childhood children require creativity from parents and educators in developing recycling-based learning media (recycle system). This study is an experimental study with the One-Group Pretest-Posttest Design model. This study uses one group and conducts a pretest before being given treatment, followed by a posttest. The sampling technique uses the technique total sampling Which covers all over child group B in Early Childhood Education RA Al-Musabbihin with 20 children. The results of the research data analysis showed a determination level of 40.6%, which means that there is a significant influence on learning media based on the recycle system on the early English reading skills of early childhood children at Paud Baitul Amal. Thus, educators can utilize the recycle system to fulfill early English reading learning media in early childhood education.